PENGUKURAN KINERJA FINANSIAL DAN NON FINANSIAL KOPERASI KSP KOPDIT TUKE JUNG - Yosef Alfian, Apriliano; Mitan, Wilhelmina; De Romario, Fransiscus (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to evaluate the financial performance using the PEARLS method (Protection, Effective Financial Structure, Asset Quality, Rates of Return and Cost, Liqudity, and Signs of Growth) and the non-financial performance using the Customer Statisfaction Index (CSI) of Tuke Jung Credit Union for the period 2020-2024. The research employed a quantitative descriptive method, utilising variables analysed, including the financial performance of the credit cooperative based on the PEARLS method, utilising 13 ratios as outlined by the Associstion of Asian Confederation of Credit Unions (ACCU). The findings indicated that the financial performance of Tuke Jung Credit Union was suboptimal, as many of the 13 ratios fell into the non-ideal category. Conversely, the CSI calculation revealed a member statisfaction level of 76,19%, indicating that the cooperative’s members were satisfied. This suggests that members are content with the services provided, reflecting a positive indicator of the credit union’s non-financial performance in meeting members’ expectations and needs.